2010
DOI: 10.1111/j.1475-6811.2010.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived community disorder, hostile marital interactions, and self-reported health of African American couples: An interdyadic process

Abstract: Using a sample of African American husbands and wives, this study investigates whether marital interactions and health are linked to their perceived community disorder. Findings suggest that only husbands' perceived community disorder is associated with their hostile behaviors toward their wives. Although wives' perceived disorder is strongly associated with husbands' perceived disorder, wives' perceptions are not directly associated with their hostile behaviors toward their husbands. Findings also suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 48 publications
(68 reference statements)
2
24
0
Order By: Relevance
“…Consistent with past cross‐sectional findings on neighborhood perceptions (Wickrama et al., ), we found that couples tended to have lower quality relationships over the first 4 years of marriage in neighborhoods where they observed more problems. Importantly, neighborhood disorder also moderated the effect of fluctuations in alcohol use, where relative increases in couple drinking were associated with marginal improvements in husband satisfaction in low‐disorder neighborhoods and marginal drops in satisfaction for wives in high disorder neighborhoods.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with past cross‐sectional findings on neighborhood perceptions (Wickrama et al., ), we found that couples tended to have lower quality relationships over the first 4 years of marriage in neighborhoods where they observed more problems. Importantly, neighborhood disorder also moderated the effect of fluctuations in alcohol use, where relative increases in couple drinking were associated with marginal improvements in husband satisfaction in low‐disorder neighborhoods and marginal drops in satisfaction for wives in high disorder neighborhoods.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, neighborhood disorder also moderated the effect of fluctuations in alcohol use, where relative increases in couple drinking were associated with marginal improvements in husband satisfaction in low‐disorder neighborhoods and marginal drops in satisfaction for wives in high disorder neighborhoods. This small moderation effect helps highlight the fact that if alcohol use has the potential to draw out both positive and negative behaviors and expressions (Jacob & Krahn, ; Leonard & Roberts, ), it will become more problematic in contexts that elicit more hostility (Wickrama et al., ). This pattern of results is consistent with the VSA model (Karney & Bradbury, ), as it presents community context as an external stressor eliciting notably different responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were gathered from 697 newlywed African American couples involved in an on-going three wave longitudinal study of African American marriage and health (see also, Stanik and Bryant 2011; Wickrama et al 2010). Participants were identified through marriage license applications filed in a southern state.…”
Section: Methodsmentioning
confidence: 99%
“…General community deviance and personal victimization both have been found to facilitate the development of negative emotions and foster a sense of loss of control over one’s life (Sieger, Rojas-Vilches, McKinney, & Renk, 2004). This may result in a heightened level of stress that can influence the behaviors that individuals direct toward their romantic partners (Beach, Smith, & Fincham 1994; Wickrama, Bryant, & Wickrama 2010). …”
Section: Introductionmentioning
confidence: 99%